THE EFFECT OF LIFESTYLE AND STORE ATMOSPHERE ON CONSUMER PURCHASE DECISIONS THROUGH PURCHASE INTEREST OF INDOMARET IN TERNATE - Ayu Qur'naesih Rusdiyanto; Ida Hidayanti; Ririn Damayanti (IAIN Surakarta, 2022)
This study aims to determine the effect of lifestyle and store atmosphere on consumer purchasing decisions through purchase interest. This research was a quantitative research. The population in this study was Indomaret consumers in Ternate City with a non-probability sampling method and a purposive sampling approach. The data analysis technique in this research used path modeling analysis using smart Partial Least Square (PLS) version 3 as a statistical test tool. The results of this study indicate that lifestyle has a significant effect on purchase decisions, store atmosphere has a significant effect on purchase decisions, lifestyle has a significant effect on puerchase interest, store atmosphere has a significant effect on purchase interest.